Coevolution of Networks and Beliefs in U.S. Environmental Risk Policy. Issue 3 (28th August 2020) - Henry, Adam Douglas; Dietz, Thomas; Sweeney, Robin L.
Abstract : Networks are an important part of the environmental policy process as they influence the ability of actors to synthesize information and learn to manage complex risks. According to the Advocacy Coalition Framework, the dynamics of policy network formation lead to structures exhibiting belief‐oriented segregation—that is, a high correspondence between shared beliefs and policy‐relevant interactions. These structures may be produced through at least two pathways: belief homophily, where actors actively seek out connections with others sharing their belief system, and policy‐oriented learning, where connected actors become more similar in their beliefs. The cross‐sectional design of much policy research does not allow an examination of these potentially complementary forces that shape belief systems and networks. These dynamics are studied using data on policy beliefs and networking in the U.S. environmental risk policy subsystem across two time periods, 1985 and 2000 (N = 223). Results indicate strong homophily effects, but relatively weak learning effects in the evolution of this policy network. This study helps pave the way for additional research on the dynamics shaping policy networks and beliefs, and helps to clarify the differences between individual versus organizational contributions to policy network evolution. Abstract : 网络是环境政策过程的一个重要部分，因为其影响行动者在合成信息、学习管理复杂风险方面的能力。根据倡导联盟框架，政策网络形成动态导致产生一系列展现以信念为导向的隔离结构，即共享信念与政策相关互动之间存在高度对应。这些结构可能通过至少两种路径方式产生：信念同质性—行动者积极寻找与其他共享其信念体系的行动者之间的联系，以及以政策为导向的学习—相连接的行动者在各自信念中变得更为相似。对许多政策研究进行的横向设计并不能对这些影响信念体系及网络的驱动力进行清晰分析，这些驱动力有可能是互补的。本文通过使用1982年和2000年（N = 223）这两段时间内美国环境风险政策子系统中的政策信念及网络的相关数据，清晰分析了这些动态。结果表明，该政策网络发展过程中出现强烈的同质性效果，但政策学习效果相对较弱。本研究帮助为今后有关政策网络及信念的形成动态的研究奠定基础，帮助阐明了个人与组织各自对政策网络发展的贡献之间的差异。 Abstract : Las redes son una parte importante del proceso de política ambiental, ya que influyen en la capacidad de los actores para sintetizar información y aprender a gestionar riesgos complejos. De acuerdo con el Marco de Coalición de Defensa, la dinámica de la formación de redes de políticas conduce a estructuras que exhiben segregación orientada a las creencias, es decir, una alta correspondencia entre creencias compartidas e interacciones relevantes para las políticas. Estas estructuras pueden producirse a través de al menos dos vías: la creencia homófila, donde los actores buscan activamente conexiones con otros que comparten su sistema de creencias, y el aprendizaje orientado a las políticas, donde los actores conectados se vuelven más similares en sus creencias. El diseño transversal de gran parte de la investigación de políticas no permite un examen explícito de estas fuerzas (potencialmente complementarias) que dan forma a los sistemas y redes de creencias. Este documento examina explícitamente estas dinámicas utilizando datos sobre creencias políticas y redes en el subsistema de políticas de riesgo ambiental de EE. UU. En dos períodos de tiempo, 1985 y 2000 (N = 223). Los resultados indican fuertes efectos de homofilia, pero efectos de aprendizaje relativamente débiles en la evolución de esta red de políticas. Esta investigación ayuda a allanar el camino para una investigación adicional sobre la dinámica que da forma a las redes y creencias de políticas, y ayuda a aclarar las diferencias entre las contribuciones individuales y las organizacionales a la evolución de la red de políticas.